Reframing Immigrant Resistance : Alliances, Conflicts, and Racialization in Italy. - Cappiali, Teresa. (Research in Migration and Ethnic Relations Series, 2019)
This book focuses on the political participation and grassroots mobilization of immigrants and ethnic minorities. Based on extensive data collected in Italy, it investigates what might explain variations in forms of political participation and grassroots mobilization at the local level.